Strategi Pengelolaan Wisata Edukatif Berbasis Sejarah di Museum Rumah Kelahiran Bung Hatta Bukittinggi - Tiara Annisa; Fresti Yuliza (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
The Bung Hatta Birthplace Museum in Bukittinggi is one of the historical destinations with great potential for history-based educational tourism. As the birthplace of the proclaimer and the first Vice President of Indonesia, this museum keeps educational values about the struggle for independence and Bung Hatta's national thinking. This research aims to identify the potential, challenges, and educational tourism management strategies at the museum. This research starts from the theory of Eduwisata from Wearing and Neil, who view eduwisata as a tourism activity that is specifically designed to provide a learning experience or a real, authentic, and meaningful learning experience for tourists, which provides interaction between tourists and the social, cultural, and natural environment, or tourist attractions that are visited. The method used is qualitative, based on direct observation, interviews with managers and visitors, documentation studies, and library studies. The research results show that the museum has fulfilled its educational function, but its management and information delivery remain conventional, so it has not optimally attracted the younger generation. Recommended strategies include increased promotion, strengthening interaction-based educational programs, utilizing digital technologies such as audiovisual and Augmented Reality, and cooperation with educational institutions. The implementation of this strategy is expected to be able to make the museum a superior educational tourist destination that plays a role in preserving history and cultivating national values.